2022
DOI: 10.3390/cells11142232
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Edible Plant-Derived Nanovesicles as Functional Food Components and Nanocarriers for Therapeutics Delivery: Potentials in Human Health and Disease

Abstract: Extracellular vesicles (EVs) are a highly heterogeneous population of membranous particles that are secreted by almost all types of cells across different domains of life, including plants. In recent years, studies on plant-derived nanovesicles (PDNVs) showed that they could modulate metabolic reactions of the recipient cells, affecting (patho)physiology with health benefits in a trans-kingdom manner. In addition to its bioactivity, PDNV has advantages over conventional nanocarriers, making its application pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…In recent years, studies have found that nano-sized EVs from plant cells have similar structures to the mammalian exosome [ 64 , 65 , 66 , 67 ], which is why these EVs are termed as “plant-derived exosome-like nano-particles” with various abbreviations, such as PDELNs [ 68 ], PLENs [ 69 ], or PDENs [ 70 ]. Other descriptive terms include “plant-derived nanovesicles (PDNVs)” [ 71 ], “plant-derived extracellular vesicles (PDEVs)” [ 72 ], “plant-derived exosomes” [ 73 ], “plant-derived edible nanoparticles” [ 74 ], or “edible plant-derived nanovesicles” [ 75 ]. This review uses the term “plant-derived exosome nanoparticles”, which is abbreviated as PDENs.…”
Section: Plant-derived Exosome-like Nanoparticle As Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have found that nano-sized EVs from plant cells have similar structures to the mammalian exosome [ 64 , 65 , 66 , 67 ], which is why these EVs are termed as “plant-derived exosome-like nano-particles” with various abbreviations, such as PDELNs [ 68 ], PLENs [ 69 ], or PDENs [ 70 ]. Other descriptive terms include “plant-derived nanovesicles (PDNVs)” [ 71 ], “plant-derived extracellular vesicles (PDEVs)” [ 72 ], “plant-derived exosomes” [ 73 ], “plant-derived edible nanoparticles” [ 74 ], or “edible plant-derived nanovesicles” [ 75 ]. This review uses the term “plant-derived exosome nanoparticles”, which is abbreviated as PDENs.…”
Section: Plant-derived Exosome-like Nanoparticle As Biomoleculesmentioning
confidence: 99%
“…Plant-derived exosome-like nanoparticles are still not as popular as mammalian-derived exosomes, which have been extensively investigated, but the research trend has been increasing [ 71 , 75 , 76 , 77 ]. This positive trend is driven by the idea that consumption of certain foods or their associated components is often linked to health benefits and disease risk reduction [ 75 ].…”
Section: Plant-derived Exosome-like Nanoparticle As Biomoleculesmentioning
confidence: 99%
“…More importantly, in 2017, the evidence from the study by Rutter and Innes [ 14 ] indicated the promising biological activity of leaf apoplast-derived EVs in the cellular defense system. Subsequently, clarifying the biological roles and clinical applications of PDEVs has rapidly become an attractive research field [ 15 ]. Recent advances in PDEVs have demonstrated their several bioactivities, such as anti-cancer, anti-inflammatory, and anti-oxidative stress properties, in vitro and in vivo [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDEVs can be obtained in large quantities due to the low cost of various plant resources. The plant-derived nanovesicles can be produced continuously from all kinds of fruits and vegetables purchased from conveniently located local markets [ 15 ]. Moreover, the plant cells in in vitro culture media could even be used to produce sufficient PDEVs [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation